Deepfake Advertising: Testing The Credibility of Sources And Messages - Sutisna Sutisna (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The use of deepfake technology has recently become more widespread, including in the use of herbal medicine advertisements. This research aims to assess the Credibility of the source and message of deepfake advertising from the perspective of viewers. This study is a survey of 185 respondents. The survey was conducted using a Google Form from May to July 2025. The data analysis method employed is a structural equation model (SEM), which utilises SMART-PLS to process the data. The results showed that the physical artefact aspect of deepfake advertising did not have a significant effect on the Credibility of the source or message. The subjective perception aspect of deepfake advertising is also stated not to affect the Credibility of the source and message. Meanwhile, the sociocultural aspect of deepfake advertising has a significant effect on the Credibility of sources and messages. Finally, the Credibility of deepfake advertising sources has a significant effect on the Credibility of the message.